ЗДОБУТКИ НАУКОВОЇ ШКОЛИ ДУХОВНОГО РОЗВИТКУ УЧНІВСЬКОЇ МОЛОДІ ПРОФЕСОРА Г.П. ШЕВЧЕНКО (Педагогіка вищої та середньої школи, 2009)
In the article light up basic directions activity of scientific school of spiritual development of student's young people G.P. Shevchenko in the making of the system of professional preparation of pedagogical personnels.